The gearing adjustment of AC 201: Comparison with SSAP 16 and Philips 1981 - M. A. Van Hoepen; I. J. Lambrechts; F. J. Mostert (South African Journal of Business Management, 1990)
The objective with this article is to analyse and compare the method of calculating the gearing adjustment as applied in the United Kingdom (SSAP 16), the Netherlands (Philips 1981 version) and South Africa (Guideline AC 201). It could be read together with Van Hoepen, Lambrechts and Mostert (1989). The gearing adjustment is an important step in inflation accounting because it recognizes the fact that a certain portion of assets could be financed in such a way that the detrimental effect of inflation is decreased. Important differences in gearing adjustment methods could result in different conclusions drawn from the analysis of financial statements and could consequently influence the financial investment decision, especially in a period of galloping inflation. The main conclusion from the comparison of the three systems is that they result in the same total adjustments over a period of time but that there are important differences over the medium and short term as well as in the present values of these adjustments. The three systems result in full capital maintenance of equity capital over time, in the case of both net monetary liabilities and assets.
Keywords: 650